Prevalence of Hypertension and Associated Factors in Lubumbashi City, Democratic Republic of Congo: A Community-Based Cross-Sectional Study - Jacques Mbaz Musung; Placide Kambola Kakoma; Clarence Kaut Mukeng; Stéphane Lubamba Tshimanga; Jeef Paul Munkemena Banze; Nathalie Kayomb Kaj; Martin Kazadi Kamuna; Jimmy Kasali Mwamba; Dophra Ngoy Nkulu; Philippe Bianga Katchunga; Olivier Mukuku; Emmanuel Kiyana Muyumba (International Journal of Hypertension)
Background. Hypertension is the leading cause of cardiovascular disease morbidity and mortality worldwide. Its struggle involves knowing its prevalence. Insufficient data on hypertension in adults in Lubumbashi, Democratic Republic of Congo (DRC), prompted the conduct of this study. The objectives were to determine the prevalence of hypertension and to identify the associated factors in adults in Lubumbashi. Methodology. A cross-sectional study was carried out among 6,708 adults from October 15th to November 24th, 2018, in Lubumbashi. Anthropometric data, lifestyle, and medical history were collected. Hypertension was defined when the mean of the last two blood pressure (BP) measurements was greater than or equal for systolic (SBP) at 140 mmHg and for diastolic (DBP) at 90 mmHg or a history of taking antihypertensive medication whatever the value of the BP. Logistic regression was used to identify the relative effects of hypertension risk factors and all statistical tests were declared significant at a p value <0.05. Results. The female participants numbered 4479 (66.8%). The mean age of all participants was 47.9 ± 16.5 years. The mean SBP and DBP were 128.4 ± 25.9 mmHg and 79.1 ± 15.3 mmHg, respectively. The overall prevalence of hypertension was 33.6%. This prevalence was statistically higher in women than in men (34.5% vs. 31.7%; p=0.024). After logistic regression, the risk of hypertension increased with age >50 years (aOR = 5.85 [5.19–6.60]), overweight (aOR = 1.25 [1.11–1.41]), obesity (aOR = 1.25 [1.11–1.41]), central obesity (aOR = 1.37 [1.16–1.61]), diabetes mellitus (aOR = 2.19 [1.63–2.95]), alcohol consumption (aOR = 1.21 [1.05–1.39]), nonconsumption of vegetables (aOR = 1.35 [1.02–1.80]), and history of stroke (aOR = 2.57 [1.88–3.51]). Hypertension was inversely associated with being underweight (aOR = 0.68 [0.53–0.87]). Conclusion. The prevalence of hypertension in the city of Lubumbashi is high as in other cities of the DRC and Africa. This situation requires the implementation of prevention, detection, and treatment programs for hypertension.